Sistem Pakar Mendeteksi Kerusakan Pada Receiver Parabola dengan Menggunakan Metode Forward Chaining Berbasis Android - Sahendra Fahreza; Sundari Retno Andani; Hendry Qurniawan; Agus Perdana Windarto; Irfan Sudahri Damanik (KLIK: Kajian Ilmiah Informatika dan Komputer, 2020)
The purpose of this research is for the damage contained in the parabolic receiver using the forward chaining method and building an appropriate and accurate expert system application to provide information about the damage that is in the parabolic receiver. Sources of data were obtained by direct interviews with the owner of the workshop, ardi, whose address was Jl. Pabatu VI Village, Kec. Dolok Merawan, Kab. Serdang Bedagai, North Sumatra. The implementation of this application is in the form of an android application. The results state that it can be applied to damage to parabolic receivers using the forward chaining method which is caused by various kinds of problems that damage users of parabolic receivers so that this application can provide information on how to handle and how to prevent it, thus helping parabolic users in symptomatic symptoms and types of systems-types of damage. the symptoms experienced by users who receive a satellite dish